THE ROLE OF FINANCIAL STATEMENTS IN INCREASING THE EFFICIENCY OF THE COMPANY MANAGEMENT ACTIVITIES - Baikadamov Nurken Turarovich,; Bolatova Botagoz Zhymabekovna,; Suleimenova Gulsim Nagmetullaevna, (Academic Journal of Physical and Chemical Sciences, 2020)
Every year, in order to improve the modern economy, it is necessary to improve the company's activities for providing services, producing products and performing works. The main tasks facing companies are to improve the conditions of transportation of manufactured products, high efficiency of the service sector, and their quality. To achieve these goals, an important role is played by evaluating the company's financial performance. This will help to develop a strategic plan for the company's development and provide a full explanation of decisions and their implementation, as well as search for sources for improving the main indicators of financial and economic activity. Currently, in assessing the company's performance, it is necessary to conduct a policy of evaluating the results of its financial and economic activities, including monitoring the activities of partners and competitors. Assesses how much they guarantee the economic interests of the company and its partners, determining the state of business activity, reliability, competitiveness and business cooperation as an important part of the effective and sustainable functioning of the company's financial position. After conducting a financial analysis of the company's activities, you can see the most important aspects of its financial condition and in what direction you need to work. After conducting a financial analysis of the company's activities, work was carried out to determine the most powerful and key aspects of the company's financial condition. Using the results obtained, we have identified many effective ways to improve the financial condition of the company's operations. The main purpose of this analysis is to timely identify and eliminate deficiencies in financial performance, find ways to prevent and eliminate them, and find sources for improving the company's financial condition.